Does the Delivery System Matter? The Scaling-Out of a School-Based Resilience Curriculum to the Social Services Sector - Lilja, Josefine L.; Kimber, Birgitta; Eriksson, Charli; Henriksson, Barbro; Skoog, Therése (Frontiers in Psychiatry, 2021)
Background: The context is highly relevant to the implementation of new health-related programs and is an implicit or explicit part of the major implementation models in the literature. The Resilience Curriculum (RESCUR) program was developed to foster the psychosocial development of children in early and primary education. RESCUR seeks specifically to decrease children's vulnerability. It aims to promote the emotional and social learning of children who may be at risk of leaving school pre-maturely, social exclusion and mental-health problems. The program is taught using a teachers' manual to support consistency of delivery, a parents' guide, and a resource package. This study aimed to examine the scaling-out of RESCUR to social services, and specifically to test if implementation differs between the school and social services sectors. Methods: RESCUR was implemented in schools and social services in Sweden 2017–2019. Data were collected via group leaders' self-reports and observation protocols for 3 months after implementation started. There were 34 self-reports from schools, and 12 from the social services sector; 30 observation protocols were collected from schools, and 10 from social services. We examined whether there were differences in implementation outcomes (in, for example, dosage, duration, fidelity, adaptation, quality of delivery) between the two delivery systems. Descriptive statistics were prepared and non-parametric tests of significance conducted to compare implementation-related factors across the two settings. Results: Analyses of both the observation protocols and group leaders' self-reports revealed that RESCUR was well-implemented in both schools and social services. The results showed a few significant differences in the outcomes of implementation between the sectors. First, regarding observations, school staff more often adapted the pace of RESCUR lessons to ensure that the children could understand than did social services staff (p < 0.01). Second, social services staff demonstrated greater interest in students and sensitivity to the needs of individual students than did school staff (p = 0.02). Regarding self-reports, social services staff reported having delivered more (p = 0.4) and longer (p < 0.01) lessons than did school staff. Second, school staff reported greater fidelity to (p = 0.02) and less adaptation of (p < 0.01) the intervention than did social services staff. Both observations and self-reports, however, indicated a high fidelity of implementation. Conclusions: Overall, the findings suggest that the resilience program, designed for delivery in schools, can be scaled-out to social services with its implementation outcomes retained. Further research is needed to test the effectiveness of the program regarding child health-related outcomes. Clinical Trial Registration: National Institute of Health, ClinicalTrials.gov, identifier: NCT03655418. Registered August 31, 2018.